Slower swimming promotes chemotactic encounters between bacteria and small phytoplankton - Riccardo Foffi; Douglas R. Brumley; François J. Peaudecerf; Roman Stocker; Jonasz Słomka (Proceedings of the National Academy of Sciences, 2025)
Chemotaxis enables marine bacteria to increase encounters with phytoplankton cells by reducing their search times, provided that bacteria detect noisy chemical gradients around phytoplankton. Gradient detection depends on bacterial phenotypes and phytoplankton size: large phytoplankton produce spatially extended but shallow gradients, whereas small phytoplankton produce steeper but spatially more confined gradients. To date, it has remained unclear how phytoplankton size and bacterial swimming speed affect bacteria’s gradient detection ability and search times for phytoplankton. Here, we compute an upper bound on the increase in bacterial encounter rate with phytoplankton due to chemotaxis over random motility alone. We find that chemotaxis can substantially decrease search times for small phytoplankton, but this advantage is highly sensitive to variations in bacterial phenotypes or phytoplankton leakage rates. By contrast, chemotaxis toward large phytoplankton cells reduces the search time more modestly, but this benefit is more robust to variations in search or environmental parameters. Applying our findings to marine phytoplankton communities, we find that, in productive waters, chemotaxis toward phytoplankton smaller than 2 μm provides little to no benefit, but can decrease average search times for large phytoplankton (∼20 μm) from 2 wk to 2 d, an advantage that is robust to variations and favors bacteria with higher swimming speeds. By contrast, in oligotrophic waters, chemotaxis can reduce search times for picophytoplankton (∼1 μm) up to 10-fold, from a week to half a day, but only for bacteria with low swimming speeds and long sensory timescales. This asymmetry may promote the coexistence of diverse search phenotypes in marine bacterial populations.